Multimedia Interaktif Infografis Desa Agro Kreatif Bingin Ambe Koripan Berbasis Android - Trisnayanti, Ni Made Ratih; Sugiartawan, Putu (INFOTEKS (Information Technology, Computer and Sciences), 2022)
This study aims to assist the management of the Agro-Creative Village of Bingin Ambe Koripan in providing a more easily understood description of the tourist objects in the village. Managers experience problems in providing clear information and designs because the majority of managers are parents who do not have expertise in design. In addition, the area of the agro-creative village which reaches 12 hectares makes it difficult for managers to provide complete information about the tourist objects in it. Therefore, the authors designed an interactive multimedia infographic application that can assist managers in providing information about this agro-creative village to tourists. The author also conducted a questionnaire to the agro-creative village manager to find out whether the application that had been made was appropriate and suitable for use in the Agro-Creative Village of Bingin Ambe Koripan. The results show that 92% of managers understand how to use the interactive multimedia infographic application that has been made and agree that this application is suitable for use in the agro-creative village.